IDENTITAS DAN STIGMA SOSIAL DALAM CERPEN "BILA JEBRIS ADA DI RUMAH KAMI" KARYA AHMAD TOHARI - Yoesoef, Mohamad (Diksi, 2020)
(Title: Identity and Social Stigma in Short Story's "Bila Jebris Ada di RumahKami" by Ahmad Tohari). Identity becomes a meaningful issue when a crisis occurs. Identity basically talks about ownership about what is generally owned and the difference with others. In the issue of identity there are problems with location, relationships, and involvement with others. The emergence of identity problems is in line with the growth of society as a consequence of migration, urbanization, and transmigration. On the other hand, the problem of identity is also triggered by awareness of gender, ethnicity, social class, and race. Therefore, identity in modern society is an important issue in the social sciences and humanities. The issue of identity in the pragmatic stage is illustrated througha variety of communities, mass media, films, or literature. Among those things, one of the potential media to express the problem of identity is literary work. There are many Indonesian literary works that question identity as an issue, one of which is a short story by Ahmad Tohari entitled "If Jebris Is in Our Home" (1991). This article discusses how the identity of a woman as a prostitute has created social problems for villagers. The social stigma is interesting to discuss from various social, religious, and human perspectives that may be interrelated or conflict with each other. The analysis of the short story shows that the resistance of the villagers to Jebris is based on religious thought and the principleof social harmony in the village.Keywords: identity, urban, religious, stigma